Crohn's disease in adults: observations in a multiracial Asian population. - Hilmi, I.; Tan, Y.M.; Goh, K.L. (2006)
AIM: To determine the demography and clinical presentation of CD and secondly to determine any differences in the prevalence between the different ethnic groups in a multiracial Asian population.